2017
DOI: 10.1093/ajcp/aqx028
|View full text |Cite
|
Sign up to set email alerts
|

Epigenetic Regulation of CD133 in Gastrointestinal Stromal Tumors

Abstract: Our results strongly suggest epigenetic regulation of CD133 expression by promoter methylation in GISTs. Pending further validation studies, high abundance of the protein can serve as a marker for malignant GISTs.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(14 citation statements)
references
References 35 publications
0
12
0
Order By: Relevance
“…DNA methylation also limits the accessibility of Sp1 and Myc to the CD133 promoter and subsequently regulate CD133 expression (Gopisetty, Xu, Sampath, Colman, & Puduvalli, 2013). Also, CD133 hypomethylation is a prognostically adverse finding in gastrointestinal stromal tumors (Geddert et al, 2017). In another study, Yi et al combined DNA methyltransferase inhibitor 5-aza-2'-deoxycytidine (DAC) and radiation for the treatment of pancreatic cancer.…”
Section: Regulation Of Cd133 Expressionmentioning
confidence: 99%
“…DNA methylation also limits the accessibility of Sp1 and Myc to the CD133 promoter and subsequently regulate CD133 expression (Gopisetty, Xu, Sampath, Colman, & Puduvalli, 2013). Also, CD133 hypomethylation is a prognostically adverse finding in gastrointestinal stromal tumors (Geddert et al, 2017). In another study, Yi et al combined DNA methyltransferase inhibitor 5-aza-2'-deoxycytidine (DAC) and radiation for the treatment of pancreatic cancer.…”
Section: Regulation Of Cd133 Expressionmentioning
confidence: 99%
“…Recently, numerous studies have implied that epigenetic alterations play critical roles in a wide range of tumours [ 9 , 10 ]. Previous studies have also demonstrated that epigenetic alterations are responsible for GIST development [ 11 ]. Both DNA hypomethylation and DNA hypermethylation are reported to be closely related to GIST progression.…”
Section: Introductionmentioning
confidence: 99%
“…Multiple transcript variants of PROM1 encoding different isoforms have been described [71]. Immunostaining in consecutive tissues using different PROM1 antibodies showed different protein expressions and characteristics [72]. GBM tumors, initiated directly from biopsies and engrafted intracerebrally into nude rats, expressed little or no PROM1 [73].…”
Section: Discussionmentioning
confidence: 99%